The Nature of the Arctic Oscillation and Diversity of the Extreme Surface Weather Anomalies It Generates - Dai, Panxi; Tan, Benkui (Journal of Climate, 2017)
Through a cluster analysis of daily NCEP-NCAR reanalysis data, this study demonstrates that the Arctic Oscillation (AO), defined as the leading empirical orthogonal function (EOF) of 250-hPa geopotential height anomalies, is not a unique pattern but a continuum that can be well approximated by five discrete, representative AO-like patterns. These AO-like patterns grow simultaneously from disturbances in the North Pacific, the North Atlantic, and the Arctic, and both the feedback from the high-frequency eddies in the North Pacific and North Atlantic and propagation of the low-frequency wave trains from the North Pacific across North America into the North Atlantic play important roles in the pattern formation. Furthermore, it is shown that the structures and frequencies of occurrence of the five AO-like patterns are significantly modulated by El Nino-Southern Oscillation (ENSO). Warm (cold) ENSO enhances the negative (positive) AO phase, compared with ENSO neutral winters. Finally, the surface weather effects of these AO-like patterns and their implications for the AO-related weather prediction and the AO-North Atlantic Oscillation (NAO) relationship are discussed. Chinese NSF [41130962, 41375060] SCI(E) ARTICLE 14 5563-5584 30